2009
DOI: 10.1177/1065912909341539
|View full text |Cite
|
Sign up to set email alerts
|

Political Integration through Ethnic or Nonethnic Voluntary Associations?

Abstract: This article challenges previous findings suggesting that ethnic associations promote political participation among immigrants. Analyzing recent survey data from Sweden, the authors find that political activity among immigrants is encouraged by associational involvement in general but not by associations based on ethnic origin. To explain this difference, the authors examine important causal mechanisms between associational involvement and political participation. They conclude that while ethnic associations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…Do the same socio-economic and demographic individual characteristics that lead natives to enter politics also matter for immigrants? Prior research on immigrant-origin populations finds that age, education, income, and employment are significant predictors of political participation, though these variables do not perform as reliably among immigrants as they do among natives (e.g., Fennema and Tillie 1999, Ramakrishnan 2005, Strömblad and Adman 2010).…”
Section: Existing Research On Immigrant Political Representationmentioning
confidence: 98%
“…Do the same socio-economic and demographic individual characteristics that lead natives to enter politics also matter for immigrants? Prior research on immigrant-origin populations finds that age, education, income, and employment are significant predictors of political participation, though these variables do not perform as reliably among immigrants as they do among natives (e.g., Fennema and Tillie 1999, Ramakrishnan 2005, Strömblad and Adman 2010).…”
Section: Existing Research On Immigrant Political Representationmentioning
confidence: 98%
“…Moreover, membership in voluntary associations has a positive effect on local political participation among Turkish, Moroccan, Surinamese, and Antillean immigrants in the Netherlands, while the results from Denmark and Belgium are less consistent across different ethnic groups. Surveying immigrants in Sweden, one study found that the effects of voluntary associations on minority political participation depend on the type of association (Strömblad & Adman, 2010). While voluntary associations encourage non-electoral political activities among immigrants, associations based on ethnic origin do not.…”
Section: Resource-based Models Of Political Participation Among Minormentioning
confidence: 99%
“…Voluntary associations' mobilizing role has also been supported by evidence from research on migrant political participation (Leighley and Vedlitz 1999;Leighley 2001;Strömblad and Adman 2011). While such studies have tried to disentangle the impact of different variables specified by prominent theories of participation, we still know little about which mechanism is responsible for the linkage between associational involvement and political participation among migrants.…”
Section: Introductionmentioning
confidence: 98%